Testing a cumulative and aggregate exposure model using biomonitoring studies and dietary records for Italian vineyard spray operators. (May 2015) - Kennedy, Marc C.; Glass, C. Richard; Fustinoni, Silvia; Moretto, Angelo; Mandic-Rajcevic, Stefan; Riso, Patrizia; Turrini, Aida; van der Voet, Hilko; Hetmanski, Michel T.; Fussell, Richard J.; van Klaveren, Jacob D.
Highlights: Tests of a new multi-source and multi-compound exposure model are presented. Comparisons cover dermal, dietary and urine samples from a biomonitoring study. Intermediate model calculations are compared with a range of existing models. Modelled cumulative dietary exposures are consistent with duplicate diet measurements. Modelled aggregate exposures are broadly consistent with field measurements. Abstract: The need for improved tools to estimate the cumulative and aggregate exposure to compounds such as plant protection products (PPPs) is recognised in the EU Regulation 1107/2009. A new model has been developed to estimate the exposure within a population to single compounds or compounds within a Cumulative Action Group, considering dietary and non-dietary sources and multiple exposure routes. To test the model a field study was carried out in Italy with operators applying tebuconazole fungicides, with measurements of dermal exposure collected. Whole urine samples were collected and analysed to provide values for the absorbed dose of tebuconazole, with duplicate diet samples collected and analysed as a measure of dietary exposures. The model provided predicted values of exposure for combined dietary and non-dietary routes of exposures which were compared to the measured absorbed dose values based on urinary analysis. The model outputs provided mean daily exposure values of 1.77 (±1.96) µg a.s./kg BW which are comparable to measured mean values from the biomonitoring field study of 1.73 (±1.31) µg a.s./kg BW. To supplement the limited measurement data available, comparisons against other models were also made and found to be comparable.